Impact of Point Defects and Oxidation on the Electronic Properties of HfS2 Monolayers. (1st January 2016) - Iordanidou, K.; Houssa, M.; Pourtois, G.; Afanas'ev, V. V.; Stesmans, A.
Abstract : In this paper, we study the structural, energetic, and electronic properties of various point defects in single-layer HfS2, using first-principles calculations. Our results show that lattice imperfections can significantly modify the electronic structure of HfS2 by introducing defect states within the gap, and pinning the Fermi level. The oxidation of both pristine and S deficient monolayers is also investigated, using first-principles molecular dynamics calculations. It is found that O atoms substitute S atoms in the lattice, forming strong Hf-O bonds, resulting in the increase of the materials energy bandgap and electron effective mass. In general, our results highlight the importance of controlling defects to achieve good performance in future HfS2 -based field effect transistors, and also provide new insights into their oxidation.